Fabrication of a Simple and Cheap Screen‐printed Silver/Silver Chloride (Ag/AgCl) Quasi‐reference Electrode. Issue 5 (2nd December 2021) - Ferreira Oliveira, Ana Elisa; Pereira, Arnaldo César; Campos de Resende, Mayra Asevedo; Ferreira, Lucas Franco
Abstract: In this work, a silver/silver chloride ink is fabricated using two steps. First the silver ink is prepare using silver, nail polish and acetone. Then the silver ink is painted in a paper substrate and a silver chloride layer is deposited using a bleach solution. The result is the silver/silver chloride conductive ink. The silver ink is cheap (2.49/g), well‐dispersive and very easy to fabricate. The materials were characterized by SEM and XRD. The Ag ink showed the formation of a continuous network throughout the silver ink film with fewer agglomeration. The effective chlorination process was also observed in the Ag/AgCl characterization. Since the Ag/AgCl substrate will be used as a quasi‐reference electrode, it is important to investigate the electrical properties. The Ag ink showed an average ohmic resistance of 2.27 Ω. The addition of the AgCl layer decreases the conductivity, as expected. In summary, the Ag/Ag/Cl ink developed is simple, well‐dispersed, cheap and with good conductivity. Therefore, it can be used as a conductive ink in the fabrication of quasi‐reference electrodes. Abstract :